ANALISIS WACANA DALAM BUKU AJAR BAHASA JERMAN DI PERGURUAN TINGGI (Journal Edutama Multidisciplinary Indonesian, 2025)
This study aims to analyze the discourse found in German language textbooks at universities, focusing on structure, communication goals, and the diversity of cultural contexts conveyed. As a teaching medium, German language textbooks play a crucial role in shaping students' understanding and language skills. In this research, a discourse analysis approach is used to identify how the textbooks present texts, dialogues, and exercises that reflect the cultural and social values embedded in the German language. The analysis results indicate that German language textbooks at universities not only function as tools for learning language structure but also as media for introducing related social and cultural contexts. This study also reveals certain patterns in the presentation of discourse that can influence how students understand and apply the German language in broader contexts. Therefore, the findings of this study are expected to contribute to the development of more contextual and relevant German language teaching methods tailored to the needs of university students.